2009
DOI: 10.1111/j.1365-3180.2009.00714.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple introductions are responsible for the disjunct distributions of invasive Parthenium hysterophorus in China: evidence from nuclear and chloroplast DNA

Abstract: Summary Parthenium hysterophorus is an invasive weed native to tropical and subtropical America. Since its introduction into China in 1926, this weed has been limited to southern areas (18°–25°N). However, new populations were recently reported in Shandong (35°N). The origin of this geographically isolated population remains unclear. In this study, we used inter simple sequence repeat and chloroplast DNA sequence markers (trnQ‐5’rps16) to investigate the genetic structure of 18 invading populations of P. hyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
3
21
2
Order By: Relevance
“…The values were much higher than in several other invasive species of Asteraceae in China Tang et al, 2009;Ma et al, 2011), and were even higher than in a previous study using inter-SSR (ISSR) markers for this species in southern China (Wang et al, 2008). Although SSR markers could reveal much more genetic variation than ISSRs, the results were unexpected for these roadside populations, which had short invasive histories (10-20 years).…”
Section: Genetic Diversity and Invasivenesscontrasting
confidence: 68%
See 1 more Smart Citation
“…The values were much higher than in several other invasive species of Asteraceae in China Tang et al, 2009;Ma et al, 2011), and were even higher than in a previous study using inter-SSR (ISSR) markers for this species in southern China (Wang et al, 2008). Although SSR markers could reveal much more genetic variation than ISSRs, the results were unexpected for these roadside populations, which had short invasive histories (10-20 years).…”
Section: Genetic Diversity and Invasivenesscontrasting
confidence: 68%
“…The AMOVA indicated that most of the genetic variation (91 %) resided within populations, rather than among populations (9 %) or among regions (highways, 0 %). The level of genetic differentiation among populations (F ST ¼ 0Á044, P < 0Á01) was much lower than the values reported for several other invasive species of Asteraceae in China Tang et al, 2009;Ma et al, 2011). Considering that the populations studied were located on the roadsides of four highways (from different directions) and were at least 40 km apart from each other, such a low level of genetic differentiation among populations was surprising.…”
Section: Genetic Diversity and Invasivenessmentioning
confidence: 58%
“…Lavergne and Molofsky 2007;Rollins et al 2009;Tang et al 2009;Gaudeul et al 2011). Lavergne and Molofsky 2007;Rollins et al 2009;Tang et al 2009;Gaudeul et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Parthenium also has the potential to build up a soil seed bank very quickly, long seed viability, luxuriant flowering, and different plants in different stages of growth,viz.vegetative, flowering, ability to seed throughout the year, to develop strong arbuscular mycorrhizal association and outcompete in ecologically diverse habitats (Navie et al, 1998). Moreover, this weed has great competitive advantage over native flora because of its low photorespiration under arid conditions, photo-and thermo-insensitivity, C 3 /C 4 intermediate mechanism, more biomass production at elevated atmospheric CO 2 concentrations as compared to the normal CO 2 concentration in a rapidly changing climate, and absence of natural enemies (Tang et al, 2009;McConnachie et al, 2011). To minimize its increasing invasiveness, quarantine measures should be adopted to check the introduction of this weed to a non-infested area through transportation of consumer goods, by movement of livestock, and flooding.…”
Section: Invasivenessmentioning
confidence: 99%